The Role of Parent-child Relationship in Parental Financial Teaching and Financial Behaviour of Students - Xolile Antoni (Journal of Consumer Sciences)
Background: The parent-child relationship plays a crucial role in facilitating financial socialisation and has been found to influence students' financial behaviour. Research on this topic, however, remains scarce despite the prevalence of poor financial literacy and risky financial behaviour among students in the Eastern Cape, South Africa. This study limited parental financial socialisation practices to financial teaching.